2009
DOI: 10.5012/bkcs.2009.30.12.2993
|View full text |Cite
|
Sign up to set email alerts
|

An ELISA-on-a-Chip Biosensor System for Early Screening of Listeria monocytogenes in Contaminated Food Products

Abstract: An enzyme-linked immunosorbent assay (ELISA)-on-a-chip (EOC) biosensor combined with cell concentration technology based on immuno-magnetic separation (IMS) was investigated for use as a potential tool for early screening of Listeria monocytogenes (L. monocytogenes) in food products. The target analyte is a well-known pathogenic foodborne microorganism and outbreaks of the food poisoning typically occur due to contamination of normal food products. Thus, the aim of this study was to develop a rapid and reliabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…66 are rapid (including loop-mediated isothermal amplification or LAMP), with total analysis time of less than one hour, but with poor LOD values near 10 2 CFU-mL -1 . The LOD can be improved considerably with sample pretreatment 67 , but this adds to the analysis time, which is not desirable in a food processing environment.…”
Section: Biosensor Characterizationmentioning
confidence: 99%
“…66 are rapid (including loop-mediated isothermal amplification or LAMP), with total analysis time of less than one hour, but with poor LOD values near 10 2 CFU-mL -1 . The LOD can be improved considerably with sample pretreatment 67 , but this adds to the analysis time, which is not desirable in a food processing environment.…”
Section: Biosensor Characterizationmentioning
confidence: 99%
“…For example, the aptamer sandwich assay developed by Lee et al [ 68 ] presented an LOD of 20 CFU mL −1 but a response time of 2 h in buffer. The lowest LOD for colorimetric sensors was 2.4 CFU mL −1 , but it required 6.5 h in buffer [ 19 ]. Few SPR-based devices for Listeria detection are found in the literature, but Boulade et al [ 69 ] recently reported a SPR-based device with a LOD of 2 × 10 2 CFU mL −1 after 7 h.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Listeria monocytogenes is the bacteria responsible for listeriosis, the third leading cause of death from food poisoning [ 11 , 12 ]. Given the transient nature of Listeria in the food chain, a variety of sensors and biosensors have been developed in the last few decades to monitor pathogens associated with food safety [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The monoclonal antibody was conjugated to the amine groups modified MPs to get IMPs, which were then blocked by PBS containing 0.5% casein to improve specificity. On the basis of IMS, the concentration of L. monocytogenes was improved more than 100 times and the detection limit of ELISA‐on‐a‐chip biosensor was as low as 54 cells/mL (Seo et al., 2009). IMPs were prepared by combining magnetic beads (M‐280) with monoclonal antibody via the streptavidin‐biotin reaction for the separation of L. monocytogenes in meat.…”
Section: The Application Of Ims In Food Microorganisms Detectionmentioning
confidence: 99%